2020
DOI: 10.3390/e22050496
|View full text |Cite
|
Sign up to set email alerts
|

On Training Neural Network Decoders of Rate Compatible Polar Codes via Transfer Learning

Abstract: Neural network decoders (NNDs) for rate-compatible polar codes are studied in this paper. We consider a family of rate-compatible polar codes which are constructed from a single polar coding sequence as defined by 5G new radios. We propose a transfer learning technique for training multiple NNDs of the rate-compatible polar codes utilizing their inclusion property. The trained NND for a low rate code is taken as the initial state of NND training for the next smallest rate code. The proposed method provides qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Jiang et al [228] A meta learning-based model independent neural decoder. Lee et al [229] Transfer learning for decoding a set of rate-compatible polar codes. Artemasov et al [230] A unified DL decoder for BCH and polar codes concatenated with CRC.…”
Section: Adaptabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang et al [228] A meta learning-based model independent neural decoder. Lee et al [229] Transfer learning for decoding a set of rate-compatible polar codes. Artemasov et al [230] A unified DL decoder for BCH and polar codes concatenated with CRC.…”
Section: Adaptabilitymentioning
confidence: 99%
“…It has been demonstrated that the proposed scheme can adapt to a channel while achieving a performance close to that of a DL decoder designed solely for the particular channel. In the same line of research, the authors in [229] proposed transfer learning to efficiently train decoders for a set of rate-compatible polar codes that are expurgated from the same mother code as in 5G NR.…”
Section: Other Approachesmentioning
confidence: 99%